A case of an unfavorable outcome of Мycoplasma pneumonia with the formation of fibrotic changes in the lungs in a child - E. V. Sharipova; I. V. Babachenko; E. A. Kozyrev; N. V. Marchenko (Детские инфекции (Москва), 2020)
Community-acquired pneumonia is a polietiologic disease and a significant cause of death worldwide. One of the pathogens of pneumonia is Mycoplasma pneumoniae, which in school-age children occupies the first place in the etiological structure, including the formation of foci of group morbidity. In most cases, mycoplasma infection has a smooth course, but possibly a protracted course with the development of progressive changes in the lungs. The aim of the work is to describe our own observation of the development of pneumofibrotic changes in a child who has undergone mycoplasma pneumonia. The article presents a description of a case of mycoplasma bronchopneumonia in a teenager, with prolonged persistence of febrile fever, catarrhal syndrome, the development of a rash in the structure of mycoplasma infection, a pronounced bilateral inflammatory process in the lungs followed by the formation of post-inflammatory changes in the form of pulmonary fibrosis, which were confirmed only by computed tomography and dynamic monitoring of the patient. Conclusion. The above example showed the need for long-term follow-up of patients with prolonged mycoplasma pneumonia by pulmonologists and the development of targeted rehabilitation.